Technological Evolution of Communication and Dissemination of Meteorological Data and Information - Chakrabarti, Dulal; Chug, Sunny; Nath, Sankar; Sai Krishnan, K. C. (MAUSAM, 2025)
150th year of the foundation of India Meteorological Department ushers in a universal acclaim for the new World Meteorological Organization (WMO) Information System 2.0 (WIS 2.0), which is the framework for Earth Systems (meteorological, hydrological, climate and ocean) data sharing in the 21st century. WIS 2.0 is a collective response by WMO member countries facing challenges to handle the 5 Vs (Volume, Variety, Velocity, Value and Veracity) of big data which, for example, for an advanced numerical weather prediction center such as ECMWF could be 1 peta (10**15) bytes daily for European Union’s Destine project which will simulate a Digital Twin (DT) of the earth to visualize high impact weather and climate changes at sub-kilometer resolution [ECMWF (2023)]. Similarly, NOAA is collaborating with Microsoft, Amazon, Google and IBM to host earth system data for any user including commercial users to generate products needed for the specific business needs [NOAA (2023)].